The Reproduction of Labour and Capital: British and Canadian Cities during Industrialization - Morris, Robert (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1989)
Urbanization in both Britain and Canada during the 19th century was associated with that intensification of capitalist relationships called industrialization. In Britain however, there were nuances worth noting. Industry migrated in from a countryside which was already full of economic activity both agricultural and industrial. Canadian urban growth took place in relatively empty economic space stimulated by the economic activity created by settler migration and commodity trade. Two important differences resulted. First, the contrast between urban and rural economic structures was much greater in Canada than in Britain, where rural community structures influenced urban social patterns. Secondly, Canadian urban centres acted as units of entrepreneur ship, within which leaders used the urban power base to attract capital and ensure its reproduction. The municipalities were weak in relation to the agents of capital with which they dealt; city councils, therefore, conceded much to manufacturers and even more to railways. The greater bargaining power of the established British urban centres showed in their relationship with the railway companies and urban utilities. British urban centres grew in a capital rich countryside. They used their urban power base to react to instabilities created by the accumulation of industrial capital, hence becoming predominantly agencies for the reproduction of labour.